Assessment of the Pain, Stress and Emotional Factor Related to the Occurrence of Bruxism - Shahpaska Budima Pejkovska (Balkan Stomatological Society, 2019)
Background/Aim: Bruxism is a parafunctional habit that has multiple etiology. Globally it is a widespread problem. The purpose of this study was to assess the presence of pain, stress and to understand the emotional factor and their relations to the occurrence of bruxism.